Tax Structure and Public Sector Efficiency: New Evidence for Developing Countries - Lucas Menescal; José Alves (Center for Economic Studies and ifo Institute (CESifo), 2023)
This study examines the effects of the tax structure composition for public sector efficiency in a sample of 41 developing countries for the period between 1997-2019. We start by calculating Public Sector Performance (PSP) composite indicators and use them as outputs to compute data envelopment analysis (DEA) efficiency scores under different orientation setups. After using a general-to-specific approach to identify the most determinant variables, we analyze the relevance of different taxes for public efficiency in a panel regression specification. We find that tax effects are significantly different depending on the orientation of DEA scores. Notably, we observe that taxation presents stronger detrimental effects to input-oriented scores in comparison to output-oriented, and that Opportunity PSP indicators seem more affected by property taxes and working contributions, while Musgravian PSP indicators are more closely related to individual and corporate income taxes. Our results allow us to provide policy implications regarding better tax structures to improve efficiency on the provision of public goods and services.
Keywords: C14; C23; H11; H21; H50; 330; public sector performance; government efficiency; tax structure; data envelopment analysis; developing countries; panel data